“Мова ворожнечі” в російсько-українській війні 2014–2015 років та національна самосвідомість українців - Гнатюк, В’ячеслав (Publishing House of Lviv Polytechnic National University, 2015)
Розглянуто проблему розширення лексичного складу “мови ворожнечі” під час російсько-української війни 2014–2015 рр. Досліджено причини поширення пейоративів із коренем “укр.” (“укри”, “укропи”) та обґрунтовано неприйнятність переймання образливої назви “укроп” свідомими українцями, а також доведено невідповідність емблем з кропом на одностроях українських вояків традиційній національній рослинній та військовій символіці. Вказано, що вживання російських нецензурних висловів в антипутінських слоганах і абревіатурах, що з’явилися під час війни 2014–2015 рр., ображають національну гідність українців, які вживають ці вирази. Іn the article the new ukrainian and russian words belonging to “hate speech” that had appeared during the Russian-Ukrainian war 2014–2015 are concerned. The conclusion is drawn that these words were created both by loyal Ukrainians and separatists of LNR-DNR along with Russian Federation citizens. The words created by Russian separatists’ participants of the conflict have more the sens of xenophobia than those from Ukrainian part. These words from the separatists’ part are: banderivtsi, banderlogi, ukry, ukropy, ukropiteki and others. From the ukrainian part the most used words are:”kolorady”, “separy”, “tery”, “lugandony”, that define ironically the separatists concerning their political position, symbolism, locality. Mostly the separatist use to call the Ukrainians as “ukropy” that sounds in Russian like homonym of the fennel. This nickname gradually forces out the other nickname “khakhly” that define the Ukrainians as the people very week and inoffensive. Now, during the war, Russian citizens and separatist saw the Ukrainians as the brave soldiers that’s wy they created the new nicknames forming them from the official name of the Ukrainian nation. But some Ukrainians liked the word “ukrop” interpreting it as abbreviation of ukrainian words “ukrainskiy opir” (ukrainian resistance) or “ukrainska opozytsiya” (ukrainian opposition). But to interpret the russian word as ukrainian abbreviation is not possible, it’s nonsense. It shows that some russian-speaking Ukrainians have the forked consciousness. It’s a result of a long colonial dependency of the ukrainian peohle from the Russian empire. That humiliating nickname is offensive for Ukrainians and it’s very strange that the command of ukrainian army introduced the image of fennel as a symbol of Ukrainian troops. That is not a traditional Ukrainian plant or military symbol. Those are mostly a bunch of guilder-rose and a kossak with a musket.
Keywords: “мова ворожнечі”; національна гідність; національна самосвідомість; “укроп”; кріп; рослинна символіка; військова символіка; “hate speech”; national self-consciousness; national dignity; “ukrop”; fennel; plant symbolism; military symbolism